Getting To Know International Civil Law: When Cross-Border Laws Meet - Muhammad Khadhaffie; Adystia Sunggara; Rahmianti Ranti Pawari (Ipso Jure, 2026)
Globalization has encouraged increasing interactions among individuals and legal entities originating from different countries. Developments in technology, international trade, foreign investment, and cross-border population mobility have given rise to various legal relationships containing foreign elements. These conditions create legal issues that cannot be resolved solely based on a single national legal system. In such circumstances, Private International Law plays a role as a branch of law that regulates private legal relationships connected to more than one country. This article aims to examine the definition, scope, fundamental principles, and role of Private International Law in resolving cross-border legal issues. This study employs a normative legal research method using statutory and conceptual approaches through library research. The findings indicate that Private International Law has an important function in determining judicial jurisdiction, the applicable law, as well as the recognition and enforcement of foreign judgments. The existence of Private International Law provides legal certainty and protection for parties involved in legal relationships containing foreign elements. As cross-border relations continue to increase, the role of Private International Law becomes increasingly important in realizing justice and legal certainty in the era of globalization.